STANDARDIZATION IN VITRO ANTIOXIDANT ACTIVITY AND BRINE SHRIMP LETHALITY OF A POLYHERBAL FORMULATION (International Journal of Ayurveda and Pharma Research, 2016)
Shakti drops an Ayurvedic polyherbal formulation is an effective medicine for immuno modulatory activity. The formulation was prepared in the laboratory with authenticated organic plant drugs. The standardization procedure was conducted on the basis of physicochemical parameters and antimicrobial studies as directed by Ayurvedic formulary of India. Antioxidant activity is further performed based on its prescribed dose in three In-vitro antioxidant models. Physical characters remained unaltered throughout study, In antimicrobial activity total aerobic count was found to be 18Ã—101 CFU/mL and total fungal count was found to be